Physicochemical, drying characteristics and rheological behaviour of foam mat-dried soursop (Annona muricata L.) powder - Vasudevan, Nanthini (2019)
Soursop is also known as Annona muricata from Annonaceae family and the fruit has been described as a sour citrus flavor. Soursop have been located in tropical regions to treat various ailments such as pain, fever, skin illness, internal and external parasites, respiratory illness, bacterial infections, inflammation, hypertension, diabetes and cancer. However, due to short shelf life of the fruit, drying process such as foam mat drying process may be an alternate method to preserve the fruit. The foam mat drying is a process in which the transformation of products from liquid to stable foam followed by air drying. The foam mat drying process is suitable for drying viscous and high fiber product at lower temperature for producing easily rehydrated juice powders. The aim of this study is to evaluate the physicochemical properties, drying characteristics and rheological behaviour of foam mat dried soursop powder. Foam mat drying was done using different foaming agent (methycellulose (MC), fish gelatin (FG) and Arabic gum (AG)) at various concentration (MC: 0.5, 10, 1.5, 2.0%; FG: 5, 10, 15, 20% and AG: 2, 4, 6, 8%). Physicochemical properties such as foam properties, bulk density, tap density, pH, moisture content, water activity, phenolic content, color and flowability of powder were analyzed. Foam mat dried powder which contains methylcellulose at 1.5% showed a better quality of soursop powder with total phenolic content 481.09±12.27 mg GAE/100g compared to other formulations; an equivalent of about 86.0% retention in its total phenolic content. The phenolic content for raw soursop fruit was 560.21 mg GAE/ 100g. The drying kinetics for foam mat drying of soursop with 1.5% methylcellulose concentration foaming agent was found to exhibit only the falling rate phase as no distinct constant rate phase was observed. Analysis on its drying rate showed that Page model represented by MR=e-kt^N (where k= 0.0035, N = 1.04) best described the drying kinetics of the foam mat drying of the soursop powder with an R2 = 0.97. The foam mat dried soursop powder with 0.5% methylcellulose was rehydrated at brix 5°, 10° and 15° to determine rheological properties at 10, 25, 35, 45 and 60 °C. The rheological modeling of rehydrated soursop foam-mat dried powder showed best fit to Power Law model.